2018
DOI: 10.14741/ijmcr/v.6.4.13
|View full text |Cite
|
Sign up to set email alerts
|

Development of Interactive Multimedia Learning to Improve Analytical Thinking Ability of Elementary School Student on Water Cycle Material

Abstract: Development of interactive multimedia is an alternative solution for learning in elementary schools that are not optimally delivered through direct observation, more precise for science learning on water cycle material that has difficulty delivered in the classroom to facilitate the achievement of basic competence that has the same achievement with 21st century competence that is analytical thinking ability. Based on this urgency, this research has a purpose to know the procedure of dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The seven studies using this design were likely to be interested in exploring the extent to which changes in AT skills can be associated with changes in other learning outcomes or identify patterns or trends in AT skills. Finally, it has been observed that the seven studies under investigation have adopted a research and development (R&D) design (Chuumchuen and Surpare, 2022; Levin and Verner, 2020; Lu Atun Nisa’ et al , 2019; Nur’Azizah et al , 2018; Rodrangsee et al , 2022; Sujatmiko et al , 2021; Thabvithorn and Samat, 2022). In the context of the research study, R&D design may be used to explore potential solutions or develop new products to enhance AT skills.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The seven studies using this design were likely to be interested in exploring the extent to which changes in AT skills can be associated with changes in other learning outcomes or identify patterns or trends in AT skills. Finally, it has been observed that the seven studies under investigation have adopted a research and development (R&D) design (Chuumchuen and Surpare, 2022; Levin and Verner, 2020; Lu Atun Nisa’ et al , 2019; Nur’Azizah et al , 2018; Rodrangsee et al , 2022; Sujatmiko et al , 2021; Thabvithorn and Samat, 2022). In the context of the research study, R&D design may be used to explore potential solutions or develop new products to enhance AT skills.…”
Section: Resultsmentioning
confidence: 99%
“…Three of these studies used constructivism theory (Anggoro et al , 2021; Khamsaengmat and Kanjug, 2022; Syaiful et al , 2021) to guide their research, while the other two used intelligence theory as their theoretical framework (Azid and Md-Ali, 2020; Rodrangsee et al , 2022). In addition, one of the studies included Dale’s Cone of experience/multimedia theory as the basis of their research (Nur’Azizah et al , 2018). Other research studies have used specific models to guide their investigations and among these frameworks are the guided inquiry model (Rodrangsee et al , 2022), the research-based learning (RBL) model (Chumsukon and Ruangsan, 2021; Suyatman et al , 2021) and the community learning resources (CLR) model (Chumsukon and Ruangsan, 2021), Focusing, exploring, analyzing, conceptual developing, and applying teaching model (Kocabaş and Yücel, 2022) and analytical thinking skills learning model (Phurikultong and Kantathanawat, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation